2022
DOI: 10.3390/antiox11122411
|View full text |Cite
|
Sign up to set email alerts
|

Improved Extraction Efficiency and Antioxidant Activity of Defatted Canola Meal Extract Phenolic Compounds Obtained from Air-Fried Seeds

Abstract: This study investigated the efficacy of roasting pre-treatment by air frying to enhance the extraction and recovery of the predominant sinapic acid derivatives (SADs) from roasted canola meal and the antioxidant potential of the methanolic extracts. Canola meal was obtained by air frying canola seed at 160, 170, 180 or 190 °C for 5, 10, 15 or 20 min. Oil was extracted using the Soxhlet method, and the de-oiled meal fraction was air-dried. Phenolic compounds were isolated using ultrasound-assisted extraction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Statistical analysis indicated that type of vegetable, method of processing and interaction between them were significant in the model statistics with an adjusted R 2 value of 0.996 (Table 1a). The previous studies by Nandasiri, et al [16] and Fadairo, et al [7,8] also showed improved TPC in canola and mustard by the application of air-frying. They observed highest TPC values for the canola meal substrate conditions at 190 o C for 15 minutes (3.15 ± 0.14 mg GAE/g DW) and 20 minutes (3.05 ± 0.02 mg GAE/g DW), respectively.…”
Section: Impact Of Thermal Processing On Total Phenolic (Tpc) and Tot...mentioning
confidence: 84%
See 2 more Smart Citations
“…Statistical analysis indicated that type of vegetable, method of processing and interaction between them were significant in the model statistics with an adjusted R 2 value of 0.996 (Table 1a). The previous studies by Nandasiri, et al [16] and Fadairo, et al [7,8] also showed improved TPC in canola and mustard by the application of air-frying. They observed highest TPC values for the canola meal substrate conditions at 190 o C for 15 minutes (3.15 ± 0.14 mg GAE/g DW) and 20 minutes (3.05 ± 0.02 mg GAE/g DW), respectively.…”
Section: Impact Of Thermal Processing On Total Phenolic (Tpc) and Tot...mentioning
confidence: 84%
“…Air-frying/roasting of the vegetables was conducted using the method described by Fadairo et al [7,8] with slight modifications. The same instant pot (Instant Pot Duo Mini 3 Qt Model number: IPDUOMINI 3Qt) was used in here with the air-fryer extension.…”
Section: Air Frying Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of phenolic compounds from oilseeds, including mustard, has been carried out for many years using a wide variety of methods in which canolol has gained considerable attention lately. Canolol is a thermally generated phenolic compound that is not naturally present (Fadairo et al., 2022; Nandasiri, Fadairo, et al., 2023; Nandasiri, Semenko, et al., 2023). However, with the application of thermal treatments, canolol is formed via decarboxylation of sinapic acid (Nandasiri, Fadairo, et al., 2023; Nandasiri, Semenko, et al., 2023).…”
Section: Introductionmentioning
confidence: 99%